Rancang Bangun Sistem Informasi Manajemen Barang dengan Fitur Pendukung Keputusan Prioritas Kebutuhan Barang Menggunakan Metode AHP-SAW - Arif Mardiyansyah; Agariadne Dwinggo Samala; Ahmaddul Hadi; Yulia Fatmi; Widya Darwin (Journal of Information System Research (JOSH), 2026)
Inventory management in government agencies often faces obstacles in determining procurement proposal priorities due to manual recording processes and subjective judgment. This study aims to design and build a web-based Inventory Management Information System integrated with a Decision Support System (DSS) using the AHP–SAW method at the Padang City Transportation Office. The system development method used is Waterfall, with the Laravel framework and MySQL database as the technological foundation. The integration of the AHP method is used to determine the criteria importance weights, while the SAW method is used to rank ten operational items alternatives. The results showed that operational urgency became the most dominant parameter with a weight of 0.557. The AHP calculation results were declared consistent with a Consistency Ratio (CR) value of 0.043. The ranking results successfully produced an objective priority sequence of goods requirements based on the combination of criteria weights and alternative values. Functional testing and comparison tests prove that the system produces outputs identical to manual calculations. The implementation of this system has successfully increased warehouse administration efficiency and provided a measurable recommendation instrument for agency leaders in preparing operational goods requirement proposals. The contribution of this study is the integration of an Inventory Management Information System with the AHP–SAW method into a single web-based platform, enabling operational inventory data to be utilized not only for inventory management but also as the basis for determining goods requirement priorities in a more objective and data-driven manner.